Implementation of PAI Curriculum Components in Improving Religious Attitudes in Students of SMP Cendekia Baznas Bogor - Annisa Siti Nurhaliza; Erihadiana; Hariman Surya Siregar (Zona Education Indonesia, 2023)
This study examines the implementation of the Islamic Religious Education (PAI) curriculum component as an effort to improve students' religious attitudes at SMP Cendekia Baznas Bogor. The research methods used were observation, interviews, and document analysis, focusing on PAI learning and how PAI curriculum components are integrated in the educational process. The results showed that the implementation of the PAI curriculum component has made a positive contribution in improving students' religious attitudes. Students at SMP Cendekia Baznas Bogor show increased understanding and awareness of religious values and are able to apply them in daily life. These findings provide important insights into the development of a more effective PAI curriculum and Islamic religious education in similar schools